Українське мистецтво другої половини XX століття: регіональні проблеми і загальний контекст (частина перша) - Скляренко, Г. (Студії мистецтвознавчі, 2009)
The article is focused on the originality of development of the Ukrainian art from the late 1950s up to the early 1980s. The author emphasizes on the differences of artistic experiences of the Western and Eastern Ukraine. The mentions of Eastern European Modernism of the 1920s–1930s remained in the Western Ukraine while the Eastern Ukraine came to it through Soviet realism. Unlike the Russian artistic development with its ‘severe style’ the Ukrainian artistic development was found in the national traditions, which had different interpretations. The author analyses the originality of the Ukrainian ‘informal art’ and its main lines as well as the differences from the art development in the West of Ukraine.